2001
DOI: 10.1093/fampra/18.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences of receiving telephone advice from a GP co-operative

Abstract: There appears to be a need for patients to be better informed about the service they can expect to receive from GP co-operatives. Recent developments such as NHS Direct may have an influence on the telephone consultation rate to GP co-operatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 5 publications
1
21
0
3
Order By: Relevance
“…These findings support those of previous qualitative studies in this area, which also found that the decision to call the out-of-hours service is complex19 20 and that home visits and swift access to medical care after initial contact are highly valued 7 8 13 20. Similarly, the sorts of issues raised are in agreement with the domains identified by McKinley and colleagues’ qualitative work conducted a decade ago 21.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings support those of previous qualitative studies in this area, which also found that the decision to call the out-of-hours service is complex19 20 and that home visits and swift access to medical care after initial contact are highly valued 7 8 13 20. Similarly, the sorts of issues raised are in agreement with the domains identified by McKinley and colleagues’ qualitative work conducted a decade ago 21.…”
Section: Discussionsupporting
confidence: 86%
“…Some patients have reported difficulty getting to treatment centres,7 8 but many appreciate the opportunity of having a prompt face-to-face consultation out of hours 8. However, telephone consultations have been consistently associated with decreased satisfaction compared with home visiting912 with some service users expressing doubts about whether an accurate diagnosis is possible over the phone 7 13. Prior expectations are important, however, and can predict overall satisfaction with out-of-hours care independent of the service type or location of care1416—for example, people who originally expected a home visit are more likely to be dissatisfied if given telephone advice 3 10 13…”
mentioning
confidence: 99%
“…Patient dissatisfaction might be related in part to the lack of knowledge about telephone triage. 25 In addition, we found that that experiences with a telephone nurse were less relevant to a follow-up contact when a patient had a subsequent consultation at a center; in the case of a home visit, experience with a telephone nurse did not predict a follow-up contact. In part this may be because patients with a face-to-face contact with a PCP have more severe health problems and a follow-up contact is necessary, regardless of the experience with the nurse.…”
Section: Comparison With Existing Literaturementioning
confidence: 78%
“…'Universal access' services -intended for both registered and unregistered patients -exist in some areas, and these may use either telephone-based or 'walk-in' access arrangements, and see patients in either hospital, NHS community dental service (CDS) or general dental surgery settings. 1 Despite this diversity in the types of out-of-hours dental care available, and a wealth of studies of different models of GP-provided out-of-hours medical care, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] there are no comparative studies that assess the effectiveness of emergency dental care provided in different ways. This study was originally designed to compare the cost-effectiveness of 'universal-access' out-of-hours dental care arrangements with 'conventional' out-of-hours care (that is, arrangements where there are separate service arrangements for registered and unregistered patients).…”
Section: Introductionmentioning
confidence: 99%